Modulated emission from dark triplet excitons in aza-acene compounds: fluorescence versus phosphorescence. (1st February 2017) - Chen, Jianwei; Chen, Yi; Wu, Yishi; Wang, Xuedong; Yu, Zhenyi; Xiao, Lu; Liu, Yanping; Tian, He; Yao, Jiannian; Fu, Hongbing
Abstract : The enhanced charge-transfer interaction from DBP to TBP leads to higher energy triplet states, which reinforces reverse intersystem crossing. Abstract : In the field of organic light-emitting diodes (OLEDs), research interests focus on making the optically dark triplet excitons shine in order to increase the electro-optic conversion efficiency of devices. In this work, two kinds of phenazine compounds, i.e. dibenzo[ a, c ]phenazine (DBP) and tribenzo[ a, c, i ]phenazine (TBP), were synthesized and used as model compounds to regulate the emission efficiency of the dark triplet excitons by chemical modification. Charge-transfer induced ultrafast intersystem crossing (CT-ISC) with a time constant of ∼1 ps was observed for these two phenazine derivatives upon photoexcitation with a high triplet yield of 77.1% for DBP and 58.7% for TBP. The triplet excited states of DBP can produce ultra-long phosphorescence with lifetime as long as 318 ms at 77 K. The quantum yield for phosphorescence ( Φ P ) is determined to be 8.45%. In sharp contrast, the triplet-excited 3 TBP* undergoes an efficient reverse intersystem crossing (RISC) process, resulting in bright delayed fluorescence emission with negligible phosphorescence. A controllable luminescence behavior from the triplet states between fluorescence and phosphorescence in phenazine derivatives is demonstrated. Theoretical calculations reveal that the structure-dependent triplet evolution is due to the charge-transfer induced energy level alignment within these compounds. Our results may have potential applications in the design of OLEDs and high triplet yield pure organic materials.